Disaggregation, auditor conservatism and implied cost of equity capital: An international evidence from the GCC - Al-Hadi, Ahmed Khamis Hamdan; Taylor, Grantley; Hossain, M. (Elsevier BV, North-Holland, 2015)
This research investigates the association between discretionary disaggregation in mandatory risk disclosures, auditor conservatism and the implied cost of equity capital. Based on a sample of financial firms from the six Gulf Cooperation Council (GCC) countries in the period 2007-2011, we find that the implied cost of equity capital is significantly negatively associated with discretionary disaggregation in mandatory market risk disclosures after controlling for firm-specific characteristics and country-specific institutional factors. Furthermore, the interaction between auditor conservatism and disaggregation in firms' mandatory risk disclosures is negatively associated with the implied cost of equity capital, suggesting that the firm disclosing more disaggregation in mandatory risk disclosure enjoys greater reduction in the implied cost of equity capital when audited by a conservative auditor. These findings are robust when subjected to a series of sensitivity tests. Collectively, these results demonstrate that more discretionary disaggregation in risk disclosures provides more private information to investors.